Effects of Annealing Temperature on Some Structural and Optical Properties of ZnO Nanoparticles Prepared by a Modified Sol-Gel Combustion Method - Zak, A.K.; Abrishami, M.E.; Abd Majid, Wan Haliza; Yousefi, R.; Hosseini, S.M. (2011)
Plate-shaped zinc oxide nanoparticles (ZnO-NPs) were successfully synthesized by a modified sol gel combustion method. Zinc acetate, pure water and isopropanol were used as the starting materials. Acetic acid, diethanolamine and nitric acid were used as the polymerization agent, complexing agent and fuel, respectively. The precursors were formed by mixing aqueous solutions of zinc acetate, acetic acid and diethanolamine. Nitric acid was used to dry the produced gel. The resulting xerogel was annealed at 600 degrees C, 650 degrees C and 750 degrees C for 1 h. The synthesized ZnO-NPs were characterized by X-ray diffraction analysis (XRD), thermogravimetric analysis (TGA) and high-magnification transmission electron microscopy (TEM). The XRD results revealed that the samples produced were crystalline with a hexagonal wurtzite phase. The TEM results showed single-crystal ZnO-NPs with nearly hexagonal plate shapes. The optical properties of the ZnO-NPs were studied by UV-visible and Fourier-transform infrared spectroscopy (FTIR). The UV-vis absorption spectra of the ZnO-NPs indicated absorption peaks in the UV region, which were attributed to the band gap of the ZnO-NPs. The results of the FTIR and UV-vis studies showed that the optical properties of the ZnO-NPs depended on the annealing temperature. (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.